“Saving vs Investing: A Comparative Study of Financial Habits” (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
This paper presents a comparative analysis of saving and investing behaviour to examine how financial literacy, income level, risk perception and demographic characteristics influence individual financial decision-making. The study is based on primary data collected from 120 respondents in selected areas of Pune city through a structured questionnaire. Descriptive statistical tools, including percentages, tables and graphical analysis, were employed to analyse and interpret the data.The results reveal that traditional saving instruments such as bank savings accounts and fixed deposits remain the most preferred avenues due to their safety, liquidity and low risk. However, an emerging inclination towards investment options such as mutual funds and equities is observed, particularly among younger and well-educated respondents. Despite this trend, investment participation is restricted by factors such as inadequate financial knowledge, fear of market volatility and limited disposable income.The study finds that a majority of respondents consider a balanced combination of saving and investing to be the most effective approach for long-term wealth creation and financial security. The paper emphasizes the need for enhanced financial literacy, early investment awareness and accessible investment products to promote informed and sustainable financial behaviour. The findings provide valuable insights for policymakers, financial institutions and educators in developing strategies to improve individual financial well-being.